Ion channel P2X7 receptor in the progression of cancer - Zhang, Guang-ping; Liao, Jun-xiang; Liu, Yi-yi; Zhu, Fu-qi; Huang, Hui-jin; Zhang, Wen-jun (Frontiers in Oncology, 2024)
P2X7 receptor (P2X7) is a non-selective and ATP-sensitive ligand-gated cation channel. Studies have confirmed that it is expressed in a variety of cells and correlates with their function, frequently in immune cells and tumor cells. We found increased expression of this receptor in many tumor cells, and it has a role in tumor survival and progression. In immune cells, upregulation of the receptor has a double effect on tumor suppression as well as tumor promotion. This review describes the structure of P2X7 and its role in the tumor microenvironment and presents possible mechanisms of P2X7 in tumor invasion and metastasis. Understanding the potential of P2X7 for tumor treatment, we also present several therapeutic agents targeting P2X7 and their mechanisms of action. In conclusion, the study of P2X7 is an important guideline for the use of clinical tumor therapy and may be able to provide a new idea for tumor treatment, but considering the complexity of the biological effects of P2X7, the drugs should be used with caution in clinical practice.